'What has Christ got to do with it?': Adaptation theory, Søren Kierkegaard and Waiting for Godot. (1st October 2018) - Norris, Marcos
Scholarship in the field of adaptation theory is divided over the issue of authorial intent. Comparing Søren Kierkegaard's reading of Genesis 22 to Samuel Beckett's Waiting for Godot, I argue that the structural and thematic similarities that mark the two stories as distinctive position Waiting for Godot as a parodic retelling of Genesis 22. The audience's adaptive experience is therefore given priority over the announced intentions of Beckett, who never intended for the play to be read as an adaptation and even warned against readings that present Godot as an analogue for God. This article offers a reader-response view of adaptation theory, arguing that certain works will be read as adaptations under the right interpretive conditions, irrespective of their authors' intentions. What matters, I conclude, is the adaptive experience, the interpreter's recognition that plot similarities and differences creatively re-envision the original work of art.